Do relationships with parents determine citizens’ reactions to war trauma? - Alicja Senejko; Ewa Gurba; Piotr Oleś; Mateusz Marek; Tomasz Franc; Krzysztof Gurba (Health Psychology Report)
Background The article concerns the psychology of trauma: the intensity of the experienced threats and reactions to the trauma in the form of post-traumatic stress disorder (PTSD), defenses and post-traumatic growth (PTG) in Ukrainian immigrants in Poland. The issues of trauma psychology were studied in connection with the relationships with parents.